A proposed education, outreach and promotion program for Ellen G. White Archives and Research Center, SDA in Cavite, Philippines - Wamalika, Martha C. (Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Promotion which is one of the principles of archives still remains a challenge to most of the archives centers today. This study focused on a church archives, EGWARC, in the Philippines, under the Seventh Day Adventist church. The Center is a branch of the Ellen G. White Estate in Maryland, USA. It serves as a special resource on the life and works of Ellen G. White, SDA history and theology to the countries in Asia Pacific. It houses copyrights of thousands of manuscripts and publications. The target groups comprised of a sample of ninety-three (93) leaders, professors/lecturers, seminarians/pastors and graduate students from Southern Asia region.